GAMBARAN FOTO TORAKS PNEUMONIA DI BAGIAN/SMF RADIOLOGI FK UNSRAT / RSUP PROF. DR. R. D KANDOU MANADO PERIODE 1 APRIL – 30 SEPTEMBER 2015 - Langke, Nurpratiwi; Ali, Ramli H.; Simanjuntak, Martin L. (Universitas Sam Ratulangi, 2016)
Background: acute lower respiratory tract Infections called (ISNBA) raises the number of pain and a high mortality and loss of productivity of work. ISNBA can be found in various forms, common is pneumonia. Pneumonia is a disease which many occurred that infects roughly 450 million people annually and occur throughout the world. This disease is a major cause of death in all groups that cause millions of deaths (7% of world total deaths) each year. This figure is most occurred in children aged less than 5 years old, and adults who are over 75 years old. Chest X-ray is the modality used to diagnose many conditions involving the thoracic wall and thoracic bone structure, located in the thoracic kavitas including the lungs, heart and great channels.Objective: to know the description of chest X-ray in people with pneumonia.Methods: This research is descriptive research study was conducted on November 2015 in Radiology Devision Faculty of medical Sam Ratulangy University/ General Hospital Center Prof. Dr. R. D. Kandou Manado.Results: there were 44 cases of pneumonia based on radiologic diagnosis. Most sufferers are male 24 people (55%), the largest age group is as many as 60 years > 12 people (27%), and the location of most pneumonia in pulmo dextra 24 cases (54%).Conclusion: Chest X-Ray images of pneumonia is more common in males withThe most dominant age is >60 years.Key Words: Pneumonia, chest X-rayLatar Belakang : Infeksi saluran napas bawah akut (ISNBA) menimbulkan angka kesakitan dan kematian yang tinggi serta kerugian produktivitas kerja. ISNBA dapat dijumpai dalam berbagai bentuk, tersering adalah pneumonia. Pneumonia adalah penyakit yang banyak terjadi yang menginfeksi kira-kira 450 juta orang per tahun dan terjadi di seluruh penjuru dunia. Penyakit ini merupakan penyebab utama kematian pada semua kelompok yang menyebabkan jutaan kematian (7% dari kematian total dunia) setiap tahun. Angka ini paling besar terjadi pada anak-anak yang berusia kurang dari 5 tahun, dan dewasa yang berusia lebih dari 75 tahun. Foto toraks merupakan modalitas yang digunakan untuk mendiagnosis banyak kondisi yang melibatkan dinding toraks, tulang toraks dan struktur yang berada di dalam kavitas toraks termasuk paru-paru, jantung dan saluran-saluran yang besar.Tujuan : Untuk mengetahui gambaran foto toraks pada penderita pneumonia.